Perceptual signs in the structure of dictionary definitions of beverages (based on the material of Ukrainian, Russian and English languages) - Zhuykova, Margaryta V.; Yodlovska, A. (Київський університет ім. Б. Грінченка, 2018)
Particular attention in linguistics is given to ways of expressing a person’s sensory perception of the world and studying the means of linguistic actualization of this process by identifying the most typical linguistic structures and models. The perceptive sign is an important component of the interpretation, because a person gains knowledge about the world through his perception with the help of the senses. The article compares the verbal description of drinks in dictionaries of different languages, which includes the inserting of perceptual characteristics in the definition and the ratio of perceptual characteristics in the structure of definitions. We have investigated that a perceptual sign helps to identify more precisely the object being described and how it is presented in the dictionaries. The words from the thematic group “drinks” explode the sensory perceptions which are received through the perceptual channels of sensation (sight, taste, smell and hearing). In our opinion, the study of the means of verbalization of perceptual features, as well as their status in the definitions of lexeme, is important because of the anthropocentric orientation of modern linguistics.
Keywords: perceptual sign; explication; thematic group “drinks”; domain; verbalization